Próba opisania świata… Świat z góry na dół w Pieczerskiej Ławrze w Kijowie Tadeusza Kubiaka - Bobryk, Roman (Tematy i Konteksty, 2017)
The article provides an interpretation of Tadeusz Kubiak’s Świat z góry na dół w Pieczewskiej Ławrze w Kijowie [The World Upside Down in Pechersk Lavra in Kyiv]. The poem presents a description of Lavra’s interior, which makes a closed and harmonious entity, “the world”. This entity is gradational rather, than homogeneous. The direction of gradation is indicated in the title and finds its embodiment on the level of style and motif. The space depicted can be divided onto two separate parts: the sacred and the profane, the boundaries of which are defined by “the wall.”